New In-Situ and Operando Facilities for Catalysis Science at NSLS-II: The Deployment of Real-Time, Chemical, and Structure-Sensitive X-ray Probes. Issue 2 (4th March 2017) - Palomino, Robert M.; Stavitski, Eli; Waluyo, Iradwikanari; Chen-Wiegart, Yu-chen Karen; Abeykoon, Milinda; Sadowski, Jerzy T.; Rodriguez, Jose A.; Frenkel, Anatoly I.; Senanayake, Sanjaya D.
Abstract : The start of operations at the National Synchrotron Light Source II (NSLS-II) at Brookhaven National Laboratory heralded a new beginning for photon-science-based research capabilities in catalysis. This new facility builds on many years of pioneering work that was conducted at the NSLS synergistically by many scientists from academia, government labs, and industry. Over several decades, numerous discoveries in catalysis were driven through the emergence of an arsenal of tools at the NSLS that exploited the power of emerging X-ray methods encompassing scattering, spectroscopy, and imaging. In-situ and operando methodologies that coupled reactor environments directly with advanced analytical techniques paved a rapid path towards realizing an improved fundamental understanding at the frontiers of chemical science challenges of the day.